Análisis jurídico de la pertinencia de la aplicación del principio de oportunidad en las contravenciones de tránsito por superar el límite de velocidad permitido en zonas no pobladas cuando no existe reincidencia, en la ciudad de Pasaje en el periodo 2013-2014. - Parra Álvarez, Vanessa Elizabeth (2016)
In this research, I have defended the idea that it is entirely appropriate to apply the principle of opportunity contraventions transit to overcome the speed limit in unpopulated areas, that under this principle is an improvement of the state towards the minimum criminal intervention and the humanization of the criminal justice system. It was shown that the effectiveness of this principle is precisely guided by the appropriate use of criminal sanctions for infringements involving transcendent injury to the social and legal order, so that the less use of criminal coercion is done, it is understood that the state is human more.